BIOMETRIA EM CLONES DE CAFEEIRO CONILON - Santos, Gleyce Pereira (2020)
SANTOS, Gleyce Pereira; M.Sc.; Federal University of Espírito Santo; December 2020; Biometrics in conilon coffe clones; Advisor: Edilson Romais Schmildt, Coadvisor: Omar Schmildt. In carrying out scientific experiments, statistics is an important point, b